Strengthening a peer mentorship program for accelerated nursing students: Development of a quality improvement pilot project - Skipper, Alexander; Jacinto, Krizalyn; Siddiqui, Salwa; Pratt, Maria; Gandza, Stephen (International Journal for Students as Partners, 2024)
In nursing education, peer mentorship programs aim to develop students’ clinical skills, encourage socialization within the program, and improve academic outcomes. This quality improvement project used the Plan-Do-Study-Act (PDSA) cycle to improve an existing student mentorship program within an accelerated nursing program in Ontario. Through a needs assessment, two areas for improvement were identified: (a) increased focus on accelerated students’ social and academic needs and (b) evaluation of the mentor-mentee interface. As the first round of changes was implemented, qualitative feedback was obtained to facilitate future improvements. Findings from this project included identifying the benefits of adopting students as partners in quality improvement and generating successful improvement strategies that cater towards peer mentorship programs for accelerated undergraduate nursing students.